KONTRIBUSI DAYA LEDAK OTOT TUNGKAI DAN KECEPATAN LARI 40 M DENGAN HASIL LOMPAT JAUH PADA SISWA SMA NEGERI 1 KUBU - Akmal '; Saripin '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The background of the problem in this study is that not all students of SMAN 1 Kubu can get target the long jump result has been specified. This problem can be seen from the observation of researchers during a lesson at school, it is suspected because of explosive power leg muscle and running speed of 40 m. Therefore, the purpose of this study was to determine whether there is a contribution explosive power legs muscle and running speed of 40 m with the long jump results of students at SMAN 1 Kubu. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As independent variables (X1) is explosive power leg muscle, (X2) running speed of 40 m while the dependent variable (Y) is long jump result. The research data was obtained from the standing broad jump test, a running of 40 m test and long jump result test squat style. Based on the research results can be concluded as follows: From the results obtained explosive power legs muscles had significant corelation with the long jump result students SMA Negeri 1 Kubu, characterized by the results obtained by the rhitung> rtabel, and has a contribution of 29%. Furthermore, from the results obtained 40M running speed had significant corelation with the long jump result students SMA Negeri 1 Kubu, characterized by the results obtained by the rhitung> rtabel, and has a contribution of 17%. Overall, there is a significant corelation between explosive power legs muscles and speed running 40 M with the long jump result students SMA Negeri 1 Kubu, characterized by the results obtained rhitung> rtabel, and has a contribution of 28%.Keywords : Explosive Power Legs Muscles, Running Speed 40 m, Long Jump